Waiting-List and early posttransplant prognosis among ethnoracial groups: Data from the organ procurement and transplantation network - Wu, Yangyang; Lv, Kaikai; Hao, Xiaowei; Lv, Chao; Lai, Wenhui; Xia, Xinze; Pang, Aibo; Yuan, Qing; Song, Tao (Frontiers in Surgery, 2023)
Background Racial/ethnic disparity in waiting-list mortality among candidates listed for kidney transplantation (KT) in the United States remains unclear. We aimed to assess racial/ethnic disparity in waiting-list prognosis among patients listed for KT in the United States in the current era. Methods We compared waiting-list and early posttransplant in-hospital mortality or primary nonfunction (PNF) among adult (age ≥18 years) white, black, Hispanic, and Asian patients listed for only KT in the United States between July 1, 2004 and March 31, 2020. Results Of the 516,451 participants, 45.6%, 29.8%, 17.5%, and 7.1% were white, black, Hispanic, and Asian, respectively. Mortality on the 3-year waiting list (including patients who were removed for deterioration) was 23.2%, 16.6%, 16.2%, and 13.8% in white, black, Hispanic, and Asian patients, respectively. The cumulative incidence of posttransplant in-hospital death or PNF after KT was 3.3%, 2.5%, 2.4%, and 2.2% in black, white, Hispanic, and Asian patients,respectively. White candidates had the highest mortality risk on the waiting list or of becoming too sick for a transplant, while black (adjusted hazard ratio, [95% confidence interval, CI], 0.67 [0.66–0.68]), Hispanic (0.59 [0.58–0.60]), and Asian (0.54 [0.52–0.55]) candidates had a lower risk. Black KT recipients (odds ratio, [95% CI] 1.29 [1.21–1.38]) had a higher risk of PNF or death before discharge than white patients. After controlling confounders, black recipients (0.99 [0.92–1.07]) had a similar higher risk of posttransplant in-hospital mortality or PNF as white patients than Hispanic and Asian counterparts. Conclusions Despite having a better socioeconomic status and being allocated better kidneys, white patients had the worst prognosis during the waiting periods. Black recipients and white recipients have higher posttransplant in-hospital mortality or PNF.